Masjid Al-Haram dan Peranannya dalam Perkembangan Awal Pendidikan dan Intelektualisme Masyarakat Melayu - Othman, Mohammad Redzuan (Jurnal Usuluddin, 2001)
The article potrays the relation between Malaya and Masjid al-Haram in Makkah in term of the development of Malay Muslim’s intelectuals and education. Historically, it has been proven that the establishment of Pondok system and then Madrasah was the direct impact of Malay Muslim. Ulama who had studied mostly in Masjid al-Haram such as Tok Kenali who has established the first Pondok in Kelantan. Those who attended Pondok’s education in Malaya at last wil pursue their halaqah study at Masjid al-Haram. Therefore this article attempts to indicate directly the role played by Masjid al-Haram to the development of Malay intelectualism and education.